Principles of Marketology. Volume 2, - Aghazadeh, Hashem (Palgrave Macmillan, 2017)
Businesses today operate in a more complex and turbulent environment and face intense competition. To be successful, businesses must intelligently understand and deal with their changing environment and market. In this book, Hashem Aghazadeh introduces marketology as a market-related system that enables businesses to achieve competitive success through providing superior value to their key stakeholders. In this regard, the hyper-function of marketology supports business executives to make effective market-related decisions and take efficient market-related actions throughout the organization. Principles of Marketology, Volume 2: Practice concentrates on how to deploy and practice marketology architecture all over the organization. Marketology accomplishes business performance and success based on its organizational design and behavior. In this regard, marketology contributes through generation, dissemination, and exploitation of market intelligence and insight. The future of marketology is contemplated and an integrated guideline of practicing marketology is provided.- Resumé vydavatel
Keywords: marketing; podnikání; konkurence; business; competition; elektronické knihy; monografie; electronic books; monographs